(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
The objective of our study is to highlight the outcome of repair of vesicovaginal fistula in a tertiary care hospital. From May’ 2013 to Dec’2014 some patents with vesicovaginal fistula underwent surgical repair in Chittagong Medical College Hospital. This is an observational study. Obstetrical complication mainly obstructed labour (98%) was the most common cause for the development of urinary fistula . Among 50 pt. (all are repaired with transvaginal approach) 41 pt —fully cured, 3 pt had urethral, incontinence. 1 pt. had vaginal stenosis, 5 pt had no successful outcome. The study concluded that genitourinary fistula is still a very troublesome complication of obstetric and gynaecoalogical procedure in developing countries. The high prevalence of vesicovaginal fistula highlights the importance of hospital delivery and the need for skilled and competent health care personal. In all case of VVF repair, proper evaluation of pt. to decide type of procedure and route of repair is essential. JCMCTA 2014 ; 25 (2) : 36-40